Tumor surgery in the pelvic region - Rahóty, Pal (Radiology and oncology (Ljubljana), 1997)
During the past ten years the authors operated on 27 tumours of the pelvic region, 12 of them involving the pelvic blade, 6 the periacetabular region, further 9 the os pubis and ischii, respectively. Most of the cases (16) were chondrosarcomas. The mean age of the patients - 13 male and 14 female - was 41years. As to surgical radicality, 11 wide, 10 marginal and 6 intralesional resections were performed. After a mean follow-up period of 3 years (0.5-11 years) 19 patients are alive and tumour-free, 2 with tumour, 4 have died and 2have been lost to follow-up. As postsurgical complication a wound-healing disorder and inguinal hernia occurred in 5 cases, surgical field thrombosis with secondary compartment syndrome and renal insufficiency developed in one case. The authors draw attention to the difficulties and indications for pelvic resections (internal hemipelvectomies).
Keywords: Bone neoplasms; Hemipelvectomy; Pelvic bones; Surgery